Effects of structure parameters on the static electromagnetic characteristics of solenoid valve for an electronic unit pump. (1st April 2016) - Sun, Zuo-Yu; Li, Guo-Xiu; Wang, Lan; Wang, Wei-Hong; Gao, Qing-Xiu; Wang, Jie
Highlights: The static electromagnetic characteristics of solenoid valve were numerically studied. The effects of driving current were considered. The effects of solenoid valve's eight essential structure parameters were considered. Abstract: In the present paper, the effects of driving current and solenoid valve's structure parameters (including iron-core's length, magnetic pole's cross-sectional area, coil turn, coil's position, armature's thickness, damping hole's position, damping hole's size, and width of working air–gap) on the static electromagnetic characteristics have been numerically investigated. From the results, it can be known that the electromagnetic energy conversion will be seriously influenced by driving current for its effects on magnetic field strength and magnetic saturation phenomenon, an excessive increase of current will weak electromagnetic energy conversion for the accelerating power losses. The capacity of electromagnetic energy conversion is also relative to each solenoid valve's parameter albeit it is not very sensitive to each parameters. The generated electromagnetic force will be enhanced by rising iron-core's length, equalizing the cross-sectional areas of major and vice poles, increasing coil turn within a moderate range, closing the coil's position towards armature's centre, enlarging armature's thickness, pushing the damping holes' positions away from armature's centre, reducing the sizes of damping holes, and reducing the width of working air–gap; but such enhancements won't be realized once the driving current is excessively higher.